Proteomics and metabolomics profiling of meat exudate to determine the impact of postmortem aging on oxidative stability of beef muscles - Derico Setyabrata; Danyi Ma; Shaojun Xie; Jyothi Thimmapuram; Bruce R. Cooper; Uma K. Aryal; Yuan H. Brad Kim (Food Chemistry: X, 2023)
The objective of this study was to characterize the major proteomes and metabolites in beef exudate and determine their relationship to color and oxidative quality of beef muscles. Beef loin (LD) and tenderloin (PM) muscles were cut into sections, individually vacuum-packaged, and aged for 9, 16 and 23 days at 2 °C. Following aging, beef exudates were collected and analyzed for both proteomics and metabolomics profiles. Proteome analysis indicated clustering by muscle types, while metabolomics profiling further clustered the samples based on the aging periods. The PM exudate had a greater concentration of oxidative enzymes, while the LD exudate contained more glycolytic enzymes. Greater lipid, nucleotide, carnitine and glucoside metabolites were observed in LD and 23d exudates. HSP70 and laminin proteins, together with glucosides metabolites, were correlated to muscle oxidative stability. The results indicated that meat exudate could be a viable analytical matrix to determine changes in quality attributes of meat with aging.